Intensive care‐treated COVID‐19 patients' perception of their illness and remaining symptoms. Issue 2 (14th November 2021) - Wallin, Ewa; Hultström, Michael; Lipcsey, Miklos; Frithiof, Robert; Rubertsson, Sten; Larsson, Ing‐Marie
Abstract: Background: The remaining symptoms in patients with coronavirus disease 2019 (COVID‐19) treated in intensive care unit are limited described. Therefore, we assessed patient's perception of their COVID‐19 disease, stay in intensive care, and remaining symptoms three to six months after intensive care. Methods: Prospective cohort study was performed in one intensive care unit of a university hospital in Sweden during the first wave. A questionnaire with open‐ended questions and closed‐ended questions was used. Data were analyzed using qualitative and quantitative content analysis and descriptive statistics. Results: Out of 123 patients treated for COVID‐19, 64 answered the questionnaire 3–6 months after discharge from intensive care. Memories from illness and hospital stay revealed in three categories; awareness of the illness, losing anchor to reality and being cared for in a dynamic environment. Information was perceived as spare by 48% and they wanted the information to be more personal. The diary was perceived as personal and was received by 33% patients. The relationship with family was affected among 39% and 13% of the patients indicated that they had not resumed their daily life. A large amount, 84%, indicated that they had remaining symptoms from COVID‐19. The dominated symptoms were impaired strength and energy both physically and mentally. Conclusion: Patients reported a variety of physical and mental symptoms, and revealed memories from the ICU, and specific awareness of other patients' health. It illustrates the need for screening patients for remaining symptoms after COVID‐19 disease and ICU care and may affect resuming patients' daily life.